PENGARUH KINERJA KEUANGAN DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wahab, Abdul; Syam, Shofiana (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2022)
This study aims to determine and analyze the effect of partially or simultaneously financial performance and Corporate Social Responsibility (CSR) on firm value at banks listed on the Indonesia Stock Exchange. Data collection using secondary data using purposive sampling technique. The population in this study is the financial statements of banks listed on the Indonesia Stock Exchange for the 2017-2019 period of 41 banks, while the sample taken is the number of observations for 3 years (2017-2019). The data obtained were analyzed using multiple linear regression analysis, t-test, F-test and the Coefficient of Determination (R²) test whose processing was carried out with the SPSS version 23 program. The results showed that the first, second and third hypotheses proposed were accepted because they showed positive and significant hypothesis test results. This means that financial performance has a positive and significant effect on firm value, Corporate Social Responsibility (CSR) has a positive and significant effect on firm value and financial performance and Corporate Social Responsibility (CSR) simultaneously has a positive and significant effect on firm value